(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Hypothyroidism can effect on the fetal outcomes during pregnancy. Objective: The purpose of the present study was to compare the effects of clical and subclinical hypothyroidism on fetal outcomes among pregnant women. Methodology: This cohort study was conducted in the Feto-Maternal Department of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from a period of 6 months dated from September 2019 to February 2020. All cases of the clinical and sub-clinical hypothyroid pregnant women admitted in this department. Fetal outcomes of clinical and sub-clinical hypothyroid pregnant women during delivery were recorded. Findings of the cases recorded carefully. Result: A total number of 75 patients were recruited for this study who were divided in to two group designated as group I or sub clinical hypothyroidism and group II or clinical hypothyroidism. Fetal distress was 22(51.1%) cases in group I and 9(33.3%) cases in group II. The fetal outcome of the study patients had observed that 8(27.6%) and 12(80.0%) of the baby had low (<2.5 kg) birth weight in group I and group II’ respectively. In group I most (62.1%) of the baby APGAR score was >7 and 11(73.3%) cases had < 6 APGAR score at 1st minute. Majority of the study patients had >7 APGAR score at 5 min in both groups which was 25(86.2%) and 12(80.0%) in group I and group II respectively. Conclusion: In conclusion there is a significant difference found in overt and sub-clinical hypothyroidism considering fetal stress, IUD and prematurity. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 29-32